EFFICACY AND SAFETY OF PEDIATRIC JUVENILE IDIOPATHIC ARTHRITIS AND UVEITIS TREATMENT WITH ADALIMUMAB - E. I. Alexeeva (Voprosy Sovremennoj Pediatrii, 2012)
The article contains results of the study of efficacy and safety of adalimumab treatment given to 110 patients with juvenile idiopathic arthritis (JIA) and arthritis with eye-lesions, refractory to classical immunosuppressive treatment. Follow up period was from 3 monthsto 1 year long. The dosage regimen was as follows — 1 subcutaneous injection of Adalimumab 40 mg once in 2 weeks. Against the background of treatment with anti-TNF agents clinical remission, decrease and normalization of lab parameters of the disease activity, lower degree of disability, quality of life increase in 100 patients (90%), decrease in uveitis activity (N = 9, 18.75%), and remission of uveitis (N=39, 81.25%) were achieved. During the follow up period there were no adverse events that lead to drug withdrawal. Thereby, Adalimumab treatment is pathogenetically justified, effective and safe for patients with JIA and uveitis.